Diet and Alzheimer's disease - Creegan, R.; McManus, Alexandra (Pan Macmillian, 2013)
Healthy eating habits are important for good health, and eating the right foods can reduce the risk of developing nutrition-related conditions such as diabetes, heart disease and some forms of cancer. Diet also plays an important part in the prevention of Alzheimer’s disease, and can improve quality of life for people with Alzheimer’s disease. This chapter focuses on the relationship between diet and Alzheimer’s disease, and how you can eat your way to a healthier life. We will also show how diet can help to prevent or delay the onset of Alzheimer’s disease, with tips about foods that can help maintain good brain health.